Deletion of the terminus region (340 kilobase pairs of DNA) from the chromosome of Escherichia coli. - Henson, J M (1985)
A strain of Escherichia coli with a 7-minute (340 kilobase pairs of DNA) deletion of the terminus region of the chromosome was isolated. This deletion was probably an IS10-promoted event and its extent was characterized by both genetic and DNA hybridization analyses. The most dramatic property of strains harboring this deletion was the absence of the sites that inhibit clockwise- and counterclockwise-traveling replication forks. These strains also grew slowly, produced many nonviable cells, were filamentous, and appeared to have an induced SOS system.